2021
DOI: 10.1080/15614263.2021.1979397
|View full text |Cite
|
Sign up to set email alerts
|

Police perceptions of eyewitness impairment due to alcohol and other drug use: a cross-cultural comparison

Abstract: Police perceptions of eyewitness impairment due to alcohol and other drug use: a cross-cultural comparison.Victims, witnesses, and suspects of crime are frequently intoxicated by Alcohol or Other Drugs (AOD) during the event. How intoxication is perceived by investigating officers, and the manner in which this is handled during interview procedures, can affect the quality of information obtained and therefore investigative outcomes. Various factors are likely to contribute to how intoxication is handled during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 33 publications
4
26
0
Order By: Relevance
“…Based on previous research (Evans et al, 2009;Crossland et al, 2018;Monds et al, 2021a;, we expected interview probability (H1a) and perceived witness credibility (H1b) to decrease as witness intoxication level increased. Due to potential lack of scientific knowledge among police officers, as suggested previously (e.g., , we expected to find an effect of the research-based message on both interview probability (H2a) and perceived witness credibility (H2b).…”
Section: Hypothesesmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on previous research (Evans et al, 2009;Crossland et al, 2018;Monds et al, 2021a;, we expected interview probability (H1a) and perceived witness credibility (H1b) to decrease as witness intoxication level increased. Due to potential lack of scientific knowledge among police officers, as suggested previously (e.g., , we expected to find an effect of the research-based message on both interview probability (H2a) and perceived witness credibility (H2b).…”
Section: Hypothesesmentioning
confidence: 99%
“…From these studies, several contributing factors to the officers' inconsistent decisions can be derived. Firstly, many police officers perceived intoxicated witnesses as less credible than sober witnesses, which may have rendered them reluctant to interview these individuals (Evans et al, 2009;Crossland et al, 2018;Monds et al, 2021a;. As the research described above has proposed otherwise, these findings suggested that police officers perhaps lacked research-based knowledge, highlighting the need for guidelines regarding intoxicated witnesses' ability to accurately recall criminal events .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations